AN EXPLORATORY STUDY OF STUDENT PERSPECTIVES ON THE BOOK "MANISNYA WARNA TULISANMU” - Tiara Alfiani; Meidawati Suswandari (Jurnal Cakrawala Pendas, 2025)
This study explores students' perspectives on the student-created book "Manisnya Warna Tulisanmu" at SDN 1 Gunungan, Manyaran. This book results from an innovative learning process encouraging students to write poetry, short stories, and coloring works. This study aims to understand how students perceive a book that contains a collection of their works in terms of its content, appearance, and usefulness in learning. The research employs a qualitative approach with an exploratory case study method. Data were collected through interviews and documentation involving students from grades 4, 5, and 6. The analysis follows Miles and Huberman’s techniques, including data reduction, display, and verification. The findings reveal that most students feel proud and motivated upon seeing their works published in the book. This book enhances their confidence and interest in writing. However, some students still experience feelings of embarrassment and lack confidence in their work. Overall, "Manisnya Warna Tulisanmu" has successfully served as a medium for appreciating and stimulating students' creativity in learning the Indonesian language.